Accuracy of Transcutaneous Bilirubinometry in Neonates Receiving Phototherapy - Dagli, Pallavi Parag; Vasava, Snehal (Journal of Nepal Paediatric Society, 2018)
Introduction: Phototherapy remains mainstay of treating neonatal hyperbilirubinemia across gestational age spectrum. Neonates under phototherapy (PTx) require frequent estimation of serum bilirubin (TSB) to monitor disease progression. Transcutaneous bilirubinometer (TcB) is widely used for estimation of TSB with limited data for neonates receiving PTx. The aim of study was to assess the diagnostic accuracy of TcB as compared to TSB in preterm and term infants receiving phototherapy. Methods: This prospective study analyzed 385 paired TcB-TSB samples from 234 hemodynamically stable preterm (89) and term (145) neonates receiving in-hospital PTx. Indigenous photo-opaque patch was applied to sternum before starting PTx. TcB was measured from patched area of skin using Dräger JM-103 device at 12 and 24 hours during phototherapy within 5 minutes of blood collection for TSB. Linear regression and Bland-Altman plots were used to compare TcB with TSB. Results: The mean (SD) gestational age and birth weight were 35.8 (2.43) weeks and 2250 (560) grams. Difference of mean of TcB and TSB was ranging between 0.7-1 mg/dl with TcB underestimating TSB. At 12 hours and 24 hours of PTx, the correlation coefficient were (r = 0.84 and 0.81, p<0.01) among preterm and (r = 0.76 and 0.79, p<0.01) among term infants. Bland–Altman plot showed significant agreement between TcB from patched site and TSB in both preterm and term neonates. Conclusion: TcB demonstrated significant accuracy in predicting TSB in both term and preterm neonates receiving PTx with slight underestimation of TSB. The study showed marginally higher correlation for preterm infants.